2012
DOI: 10.1016/j.seizure.2012.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Circadian patterns of generalized tonic–clonic evolutions in pediatric epilepsy patients

Abstract: GTC evolution occurs most frequently out of sleep and in older patients. Our results may assist in seizure prediction, individualized treatment patterns, and potentially complication and SUDEP prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 13 publications
1
24
0
Order By: Relevance
“…Most of the original studies described an increased seizure occurrence in the (early) morning compared to the rest of the day, both in epilepsy populations of all ages [31,34,35] and in cohorts including children [32,33,[36][37][38][39] or adults separately [40]. Many also reported a peak at varying times in the afternoon or the evening [32-37,39-45].…”
Section: Circadian Seizure Distributionmentioning
confidence: 99%
“…Most of the original studies described an increased seizure occurrence in the (early) morning compared to the rest of the day, both in epilepsy populations of all ages [31,34,35] and in cohorts including children [32,33,[36][37][38][39] or adults separately [40]. Many also reported a peak at varying times in the afternoon or the evening [32-37,39-45].…”
Section: Circadian Seizure Distributionmentioning
confidence: 99%
“…SUDEP is thought to occur more frequently during sleep, suggesting a possible causal association. Sleep-related ictal phenomena, such as preferential seizure occurrence and secondary generalization in some populations could favor the pathophysiological mechanisms leading to SUDEP (Nobili et al, 2011; Ramgopal et al, 2012), Sleep-related environmental factors, such as lack of supervision at night, may also play a role (Ryvlin et al, 2013a; Lamberts et al, 2012). …”
Section: Future Directions: Utilizing Regulatory System Relationshimentioning
confidence: 99%
“…In fact, two studies that examined this question [16,17] found a larger percentage of unrecognized seizures if the patients were asleep at the time of seizure onset. The reason for the difference in seizure report could be, in part, attributed to the fact that seizures occurring during sleep are more often secondarily generalized [31,32], therefore, possibly affecting the ability of patients to be aware of their seizures. However, one study showed that 86% of simple partial seizures occurring during sleep were undocumented by patients [16].…”
Section: Sleep/wake State At Time Of Seizure Onsetmentioning
confidence: 99%